Comparison and analysis of the use of systematic review and scoping review in the area of patient care in Pharmacy (Research, Society and Development, 2021)
This study aims to describe and compare two review methods - systematic and scoping - in addition to analyzing the use of these methods in studies in the area of ​​patient care in pharmacy. The articles used to support this work were selected from the following databases: Google scholar, PubMed, and Scielo. The study was divided into two stages: 1) Description and comparison of two literature review methods: systematic review and scoping review; 2) Analysis and comparison of the use of scoping and systematic reviews in the area of ​​patient care in Pharmacy. It was found that the methods for preparing the studied reviews follow a systematic and well-structured process, but they differ in terms of some methodological elements not observed in the scoping review, such as quality assessment of included studies and more advanced statistical analyses. The systematic review analyzed, unlike the scoping review, did not meet the criteria proposed for its preparation in the stages of selection and evaluation of the quality of studies. It is concluded that, although the reviews are aimed at different objectives, both present a careful methodology. Correctly associating the research question with the type of review is crucial for conducting the study.